Pembatalan Izin Poligami di Pengadilan Tinggi Agama Maluku Utara - Rugaya Alkatiri; Abu Sanmas (Indonesian Journal of Shariah and Justice, 2021)
This study was conducted to Analyze and Correct the verdict No: 41/Pdt.G/2007/PA. Tte and Verdict No: 12/Pdt.G/2007/PTA. MU, which is the consideration of the Judges of the Ternate Religious Court and the North Maluku Religious High Court against the Verdict on polygamy permit cases that occurred in North Maluku Province. The Research Method used is Literature Research, namely: Activities to obtain Information relevant to the Consideration of judges of the Ternate Religious Court and the North Maluku Religious High Court against the ruling of polygamy permit cases. The result of this study is that the case of the Polygamy Permit Application filed by the F.A. who is domiciled as the Applicant, where the Judge in the First Level looks at the Sitting Case and Its Legal Considerations, so that the Panel of Judges in the First Level Court granted the Polygamy Permit Application. While at the Court of Appeal filed by M.A. who is domiciled as the Respondent at the First Level, but in the Appeal Level M.A domiciled as a Comparison, but in the Decision of the Panel of Judges at the Appeal Level by looking at the Sitting Case and Legal Considerations that the Verdict at the First Level is not acceptable on the grounds that the polygamy application case is a Case that is Voluntair (unilateral) not Contentiosa (has opponents where The existence of the Respondent, the First Wife) then the case is considered Obscur Libel (Escape), because the Lawyer does not include the name of the Prospective Wife of the Applicant orbanding in the contents of the Application at the First Level and on the Counter Memory Appeal so that the Panel of Judges decides the Case is unacceptable.